Development of Health Promotion-Based Education Methods to Increase Accessibility of Adolescent Mental Health - Sari Br Sembiring, Isyos; Natalia Br Sinuhaji, Lidya; Manurung, Basaria; Suyanti Damanik, Nopalina; Ginting, Perkasa; Kristina Pangaribuan, Ingka; Mandala Putri Sembiring, Ninsah; sadarni gulo, Lusia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Good health and well-being are still significant problems in the world of health and are top priorities in health goals in the short and long term. Mental health disorders or depression are mental problems that are one of the factors that have not achieved a level of health in Indonesia and the world, so the transformation of adolescent mental health continues to be carried out throughout the world (1). Mental health is very vulnerable to teenagers. WHO data (2022) states that 1 in 7 children aged 10-19 years are known to experience psychological problems. The prevalence rate for mental health disorders in Asia ranges from 1.81% to 23.3%. (2) Data in Indonesia shows that 6.1% of the Indonesian population aged 15 years and over experiences mental health disorders. According to the 2022 Indonesian National Adolescent Mental Health Survey (I-NAMHS), as many as 15.5 million or 1 in 3 adolescents (34.8%) in Indonesia experience mental health. This research aims to analyze the development of health promotion-based education methods to increase the accessibility of adolescent mental health in Bangun Rejo Village. (b) To determine the feasibility of health promotion-based education methods to increase the accessibility of adolescent mental health in Bangun Rejo Village. The research method used is Research and Development, with stages of analyzing the method to be developed, the method development process, product testing, and the revision and evaluation stage to improve method weaknesses. The research results on developing health promotion-based education methods to increase mental health accessibility among adolescents in Bangun Rejo Village show that the results of the first hypothesis test are accepted, namely that there is an influence between self-awareness and self-awareness. Emotional and mental regulation of teenagers in Sudi Rejo Village, Tanjung Morawa District, means higher self-awareness. A person has higher emotional and mental regulation, and the development of Health Promotion-Based Education Methods, namely self-awareness and self-efficacy, increases the accessibility of adolescent mental health.